Delays in Leniency Application: Is There Really a Race to the Enforcer's Door? - Dennis L. Gärtner; Jun Zhou (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
This paper studies cartels' strategic behavior in delaying leniency applications, a take-up decision that has been ignored in the previous literature. Using European Commission decisions issued over a 16-year span, we show, contrary to common beliefs and the existing literature, that conspirators often apply for leniency long after a cartel collapses. We estimate hazard and probit models to study the determinants of leniency-application delays. Statistical tests find that delays are symmetrically affected by antitrust policies and macroeconomic fluctuations. Our results shed light on the design of enforcement programs against cartels and other forms of conspiracy.
urn:nbn:de:bvb:19-epub-14315-4
Keywords: D43; K21; K42; L13; 330; corporate leniency program; cartel; leniency application delays